Analisis Nilai-nilai Pendidikan Karakter dalam Film Animasi Kabi Karya Educa Studio - Rona Fitriatul Inayah; Sita Husnul Khotimah; Rokimin (La-Tahzan: Jurnal Pendidikan Islam, 2026)
Character education plays an important role in shaping children's personalities amid the rapid development of digital media. Not all media content, especially animated films, contains educational values; some even present negative behaviors that may be imitated by children. Therefore, alternative media that is both entertaining and educational is needed, such as the animated film KABI: Kisah Teladan Nabi, which contains Islamic values. The purpose of this study is to identify the character education values in the KABI animated film and to analyze their relevance to Islamic education. A qualitative approach was employed using library research and content analysis methods. The data were obtained from selected episodes of the KABI animated film and analyzed through documentation techniques. The results show that the film contains twelve character education values, namely religiosity, reading interest, social awareness, curiosity, hard work, responsibility, honesty, environmental awareness, tolerance, discipline, independence, and appreciation of achievement. These values are relevant to Islamic education, encompassing aspects of aqidah, sharia, and akhlaq. Thus, the KABI animated film can serve as an educational medium for instilling Islamic character values in children.